2022
DOI: 10.1039/d1qi01164b
|View full text |Cite
|
Sign up to set email alerts
|

The reaction mechanism of acetylene hydrochlorination on defective carbon supported ruthenium catalysts identified by DFT calculations and experimental approaches

Abstract: It is critical to identify the reaction mechanism of carbon supported metal catalysts for the exploration of high-performance catalyst in acetylene hydrochlorination. Herein, we reported a systematically study on the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…All theoretical calculations presented in this paper are based on Density Functional Theory (DFT). [18][19][20] The first-principles calculations for the periodic 3BQ system were conducted using the Vienna Ab initio Simulation Package (VASP) software. [21][22][23][24] The electronic interaction was described using the projector augmented wave (PAW) method.…”
Section: Computational Detailsmentioning
confidence: 99%
“…All theoretical calculations presented in this paper are based on Density Functional Theory (DFT). [18][19][20] The first-principles calculations for the periodic 3BQ system were conducted using the Vienna Ab initio Simulation Package (VASP) software. [21][22][23][24] The electronic interaction was described using the projector augmented wave (PAW) method.…”
Section: Computational Detailsmentioning
confidence: 99%
“…All calculations involved in this study were performed by DFT calculations with the Gaussian 16 package. 42 DFT calculations have been widely used in mechanism [43][44][45][46][47][48] and aromaticity 39,49,50 studies. The geometries of all complexes in their lowest singlet and triplet states were optimized using the (U)B3LYP 51,52 method in the gas phase.…”
Section: Computational Detailsmentioning
confidence: 99%
“…[16][17][18] Additionally, some reports indicated that the redox voltage of organic molecular crystals could be reliably predicted by first-principles calculations. [19][20][21] In contrast, few theoretical research studies focused on the sodiation process of single-molecule organics in non-periodic systems.…”
Section: Introductionmentioning
confidence: 99%
“…16–18 Additionally, some reports indicated that the redox voltage of organic molecular crystals could be reliably predicted by first-principles calculations. 19–21 In contrast, few theoretical research studies focused on the sodiation process of single-molecule organics in non-periodic systems. Unfortunately, these small-molecule organic materials cannot be investigated by the abovementioned crystal simulation methods, despite having excellent potential for sodium storage.…”
Section: Introductionmentioning
confidence: 99%